种利用超临界二氧化碳制备离聚体的方法 (2018)
本发明提供种利用超临界二氧化碳制备离聚体的方法，包括如下步骤：(1)将具有-COOH酸性基团的聚合物和碱性盐加入超临界反应釜中；(2)向所述超临界反应釜中冲二氧化碳1-20min，以排出所述超临界反应釜中的空气，然后关闭所述超临界反应釜的出口阀；(3)用高压泵将二氧化碳加入所述超临界反应釜中，同时将温度升至40-100℃，使压力达到8-30MPa，然后反应0.5-2h；(4)降温泄压后收集产物，所述超临界反应釜中的二氧化碳经干燥回收后可以重复使用。本发明不需要采用有机溶剂，具有环境友好型、无毒、不易燃烧等特性，且溶剂二氧化碳方便回收利用。 The invention provides a method for preparing an ionomer by utilizing supercritical carbon dioxide. The method comprises the following steps: (1) adding a polymer with a -COOH acid group and a basic salt into a supercritical reaction kettle; (2) introducing carbon dioxide into the supercritical reaction kettle for 1-20 minutes so as to discharge air in the supercritical reaction kettle, and closing the outlet valve of the supercritical reaction kettle; (3) adding carbon dioxide into the supercritical reaction kettle by using a high-pressure pump, and heating to the temperature of 40-100 DEG C so as to achieve the pressure of 8-30MPa, and reacting for 0.5-2 hours; and (4) cooling, decompressing and collecting the product, wherein carbon dioxi